Applications of Fuzzy Baire Spaces - E. Poongothai; M. Nalini (International Journal of Mathematics And its Applications, 2025)
The fuzzy sets, in which the elements of the universe have their membership and non-membership degrees in [0,1] is of Zadeh's fuzzy set. In this paper fuzzy sets are used as tools for assessment and decision making. This is useful in cases where one is not sure about the suitability of the linguistic characterizations assigned to each element of the universal set. Applications illustrating our results are also presented.